КОРПОРАТИВНА КУЛЬТУРА ПІДПРИЄМСТВА В УМОВАХ ПАНДЕМІЇ - Banit, Olga (Zhytomyr Ivan Franko State University, 2022)
The coronavirus pandemic has caused a crisis in business. Under such conditions, special attention was paid by the management of enterprises to raising the level of corporate culture. One of the challenges for business has been the transition to remote work or the impossibility of such a transition, a sharp increase in the number of layoffs and economic downturns in many areas. The deterioration of social ties that strengthen the corporate culture has become one of the threats to it. The main task of the management was to preserve human capital and support staff. The article considers the positive transformations of the traditional model of corporate culture. Its flagships are trust, honesty, openness and transparency in communication, flexibility. Among the negative changes in the corporate culture, employees attributed the lack of flexibility, unwillingness of enterprises to adapt to new conditions. The ethics with which the management reacted to the changes due to the pandemic also received a positive assessment. According to workers, the recession, economic uncertainty, political unrest and mass protests have a negative impact on companies' ability to respond to change through a pandemic. Corporate culture is seen as a system of values ​​that is common to all employees and management. It is a set of rules developed by a group of people while adapting to environmental conditions. Corporate culture can be conservative, or it can be innovative and create new conditions for enterprise development. Thus, the corporate culture of the enterprise can and should be transformed to adapt to the crisis of the external environment. Corporate culture is designed to ensure employee loyalty and high profits, effective interaction and increase productivity. Studies show that some companies have been unable to respond to changes due to the pandemic, but most companies plan to continue to use the strategies and tools implemented during quarantine.